The Role of Guidance and Counseling Teachers in Enhancing the Job Readiness of Vocational High School Students: A Systematic Literature Review - Oktaviana, Trya Achdisty; Suherman, Uman; Hakim, Ibrahim Al (Pusdikra Publishing, 2026)
Work readiness is one of the key competencies for vocational high school (SMK) graduates to enter the dynamic world of work in the era of the Fourth Industrial Revolution and Society 5.0. Guidance counsellors have a strategic role in facilitating work-readiness through orientation services, career information, group guidance, individual counselling, and collaboration with the business and industrial worlds. This article aims to systematically analyse the results of recent research on the role of guidance counsellors in improving the work readiness of SMK students. The study used a Systematic Literature Review (SLR) design with the PRISMA 2020 guidelines. Articles were searched for through Google Scholar, the SINTA-indexed national journal portal, DOAJ, and university repositories for the period 2020–2025. From the initial 50 documents, across the identification, screening, eligibility assessment, and inclusion stages, 20 empirical studies were analysed. The synthesis results showed five main themes of the role of guidance counsellors, namely: (1) strengthening motivation and work attitude, (2) career information and planning services, (3) facilitation of Special Job Fairs and industrial work practices, (4) development of employability skills and digital literacy, and (5) counselling and group guidance interventions targeting career self-efficacy and work readiness. These findings confirm that guidance counsellors play the roles of career educators, career coaches, and career facilitators, and that they need to be supported by a strong guidance counselling management system integrated with link-and-match policies for vocational education.